2022
DOI: 10.1108/itp-01-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Virtual meetings and wellbeing: insights from the COVID-19 pandemic

Abstract: PurposeThe purpose of this paper is to examine the relationship between virtual meeting participation and wellbeing. Based on the conservation of resources theory, we hypothesize that participation in more virtual meetings is associated with both negative and positive wellbeing indicators.Design/methodology/approachAn online survey was sent to 3,530 employees across five Belgian universities in April 2020. Useful data from 814 respondents was collected and analyzed to test the hypothesized relationships.Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…In sum, the benefits of smart working are epitomized by schedule and location flexibility, technology that streamlines work, and processes that promote a work-life balance (WLB). As mentioned, smart working can positively influence workers' performance and, in general, their wellbeing, reducing work-family conflict [14][15][16]. Conversely, its drawbacks are associated with increased work intensity, limited workspaces, technostress, isolation, and an intensified domestic and caregiving workload [22].…”
Section: The Moderating Effect Of Quality Of Smart Working Between Wo...mentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, the benefits of smart working are epitomized by schedule and location flexibility, technology that streamlines work, and processes that promote a work-life balance (WLB). As mentioned, smart working can positively influence workers' performance and, in general, their wellbeing, reducing work-family conflict [14][15][16]. Conversely, its drawbacks are associated with increased work intensity, limited workspaces, technostress, isolation, and an intensified domestic and caregiving workload [22].…”
Section: The Moderating Effect Of Quality Of Smart Working Between Wo...mentioning
confidence: 99%
“…Nevertheless, previous research has indicated that the shift to smart working can yield both positive and negative outcomes. On the one hand, it has been noted that, under certain conditions, smart working can enhance performance and wellbeing by reducing the conflict between work and family [14][15][16]. On the other hand, this transition has introduced new challenges, including social isolation, difficulties in disconnecting, unsuitable tools for meeting objectives, enforced cohabitation, and diminished organizational support, which also encompasses communication challenges with supervisors and colleagues [17].…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, almost all organizations, especially public administrations, have had to face a transition to smart working that has allowed them to continue their activities and avoid contagion (Di Tecco et al 2021;Rapisarda et al 2021). These forms of work organization, based on flexibility and autonomy and characterized by the absence of time or space restrictions and an organization by processes and objectives, have been a necessity during the COVID-19 pandemic and have not always had negative effects or results (Angelici and Profeta 2023;Darouei and Pluut 2021;Heiden et al 2021;Standaert et al 2023). Todisco et al (2023) have conducted research to assess workers' experiences in the public sector with smart working before and after the pandemic.…”
Section: Introductionmentioning
confidence: 99%